2015
DOI: 10.1063/1.4929861
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Kelvin magnetic and electrical measurements in a diamond anvil cell with in situ tunability

Abstract: We discuss techniques for performing continuous measurements across a wide range of pressure–field–temperature phase space, combining the milli-Kelvin temperatures of a helium dilution refrigerator with the giga-Pascal pressures of a diamond anvil cell and the Tesla magnetic fields of a superconducting magnet. With a view towards minimizing remnant magnetic fields and background magnetic susceptibility, we characterize high-strength superalloy materials for the pressure cell assembly, which allows high fidelit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…To further expand the parameter space, a natural addition would be a vector magnetic field H, leading to a much broader (H, P, T) phase space. It has been shown that a diamond-anvil cell can be made fully out of non-ferromagnetic materials with very low magnetic permeability (Palmer et al, 2015). The major remaining technical challenge is to manufacture a superconducting magnet, presumably using high-T c cuprate ribbons, that would be thermally anchored at the first cooling stage of the Gifford-McMahon cryostat ($50 K).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further expand the parameter space, a natural addition would be a vector magnetic field H, leading to a much broader (H, P, T) phase space. It has been shown that a diamond-anvil cell can be made fully out of non-ferromagnetic materials with very low magnetic permeability (Palmer et al, 2015). The major remaining technical challenge is to manufacture a superconducting magnet, presumably using high-T c cuprate ribbons, that would be thermally anchored at the first cooling stage of the Gifford-McMahon cryostat ($50 K).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of experimental techniques have been developed to probe both ground states and excitations of ion, charge and spin degrees of freedom in a DAC-based pressure environment. These include electrical transport (Derr et al, 2008;Jaramillo et al, 2010), AC magnetic susceptibility (Debessai et al, 2009;Palmer et al, 2015) and heat capacity/calorimetry (Demuer et al, 2000) for studying the bulk properties of materials under pressure. Nuclear magnetic resonance (Eremets, 1996), Mö ssbauer spectroscopy (Bi et al, 2016), X-ray magnetic dichroism (Duman et al, 2005) and fluorescence (Bi et al, 2016), as well as optical probes (Eremets, 1996), allow characterization of local behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Probably, their peaks are hidden by the micro-texture, since in the X-ray powder diffraction pattern reported in Ref. [13] the peaks of the three phases are clearly seen. The measurements show that the lattice parameter of the Ni rich phase is distorted with respect to the pure Ni compound, being actually a = 3.57 Å.…”
Section: Russian Alloymentioning
confidence: 94%
“…The Cr rich phase, almost depleted of Ni, has a BCC crystal structure, with a = 2.91 Å. The Ni 3 Al phase has a cubic FCC structure, with the Al located at the cubic unit cell vertices and the Ni at the faces, and its lattice parameter is a = 3.56 Å [13]. The diffraction patterns of the two NiCrAl alloys (cylindrical bars of 12 mm φ and 18 mm φ), obtained from the measurements at LET, are displayed in Fig.…”
Section: Russian Alloymentioning
confidence: 99%
“…AC magnetic susceptibility measurements at a probe field of 0.5 Oe were carried out using a diamond anvil cell designed for rapidly exploring H-P-T parameter space [24]. Sapphire seats and thermally-hardened BeCu or MP35N gaskets were used to avoid any ferromagnetic background disturbance to the superconducting transition [24,25]. Four different crystals were studied in a Methanol:Ethanol 4:1 hydrostatic pressure medium.…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%